Genetic association study between Interleukin 10 gene and dental implant loss - Pigossi, Suzane C. [UNESP] (2012)
Objective: Three single nucleotide polymorphisms (SNPs), -1082, -819 and -592, located on the promoter region of IL10 gene have been associated with high in vitro IL-10 production and autoimmune diseases. We aim to investigate whether polymorphisms in the IL10 gene would influence dental implant loss.Methods: We evaluated a total of 277 unrelated patients, including 185 individuals presenting at least one osseointegrated implant in function for six months or more and with no implant failure, and 92 individuals presenting at least one implant loss. DNA was extracted from buccal mucosa cells and SNPs were genotyped using TaqMan (R) probes-based assays.Results: Multiple logistic regression showed association between dental implant failure with -819(C/T) genotype (OR = 3.27; 95% CI = 1.02-10.46; p = 0.0334). However, considering the statistical significance level alpha = 0.004 (adjusted by Bonferroni correction of multiple comparisons), these results lost their significance. No association of dental implant loss with genotypes and alleles of the -1082 and -592 SNPs, as well as IL10 haplotypes in genotype/allele forms were found (p = 0.9400; p = 0.8861).Conclusions: Neither the IL10 gene polymorphisms, nor haplotypes or other covariates were associated with susceptibility to dental implant failure in the studied population. (C) 2012 Elsevier Ltd. All rights reserved.